2018
DOI: 10.1111/obr.12760
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood social capital and obesity: a systematic review of the literature

Abstract: Summary Social capital, defined as the resources accessed by individuals and groups through social connections, has been posited to be a social determinant of obesity. However, empirical evidence for this association has been inconsistent – namely, some studies have found a protective association while others have reported no correlation. We sought to conduct a systematic review on the relation between neighbourhood social capital and obesity, considering potential differences on the results based on the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 72 publications
(183 reference statements)
4
46
2
Order By: Relevance
“…With its potential role on social connectedness already recognised (related to the attribute "food: the glue of social connectedness") [21], eating behaviours are closely connected with social attitudes and practices. Vast research identifies social factors such as social and mass media, market globalisation, and economic growth as drivers for individual and social behaviours, greatly influencing health and dietary-related practices [49,50]. This influence of the social context on diverse food-related aspects (such as food choices) can either be supportive of a healthful eating approach (linked to the attribute "social support") or depict a barrier to the endorsement of a balanced food intake (related to the attribute "eating socially: gateway for unhealthier choices").…”
Section: Influential Factors Of Food Literacymentioning
confidence: 99%
“…With its potential role on social connectedness already recognised (related to the attribute "food: the glue of social connectedness") [21], eating behaviours are closely connected with social attitudes and practices. Vast research identifies social factors such as social and mass media, market globalisation, and economic growth as drivers for individual and social behaviours, greatly influencing health and dietary-related practices [49,50]. This influence of the social context on diverse food-related aspects (such as food choices) can either be supportive of a healthful eating approach (linked to the attribute "social support") or depict a barrier to the endorsement of a balanced food intake (related to the attribute "eating socially: gateway for unhealthier choices").…”
Section: Influential Factors Of Food Literacymentioning
confidence: 99%
“…Research on neighbourhoods and their influence on obesity focus on the physical environment, including the food and physical activity environments, as well as the social environment,1 2 which refers to the social interactions (or lack thereof) that occur in the neighbourhood between neighbours. The social environment includes concepts like social cohesion and social ties, as well as exposure to crime and violence, all of which have been linked to obesity 3 4. Neighbourhood social cohesion is hypothesised to work as a buffer for stress and, as such, to be protective of obesity,5 whereas neighbourhood crime and violence may affect the likelihood of outdoor physical activity6–8 and, through this mechanism, be detrimental for obesity.…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal evidence on whether changes in social capital and social support are associated with changes in PA is still scarce, in particular in young people and outside of the USA. 19 21 22 The few available longitudinal studies are generally consistent with cross-sectional results and found positive associations between baseline/change in the social environment and change in PA. Much of the literature, especially on social capital, captures total PA or leisure-based PA and does not explore whether a specific aspect of social context could differentially affect a range of forms of PA, such as outside play, structured activities or walking to school. There is also limited evidence as to whether the positive associations observed for the general population are consistent among ethnic minority and deprived populations.…”
Section: Introductionmentioning
confidence: 52%